Cellulose-based adhesives: From molecular mechanisms to emerging applications - Shijie Du; Guangyi Li; Yixin Zhu; Yingxuan Shi; Ruohan Cao; Suiyi Li; Changlei Xia (Chemical Engineering Journal, 2026)

Effects of microsized and nanosized polystyrene on detrital processing and nutrient dynamics in streams - Jingjing Du; Mengxi Gao; Zhi Rao; Xun Zhou; Yan Su; Jianguo Zhao; Jianxiang Lv; Ruohan Mao; Yuran Song; Xia Cao (Environmental Pollution, 2026)

Long-term exposure to dust in fine particulate matter and post-stroke functional impairment—Findings from the China National Stroke Screening Surveys - Zhaoyang Pan; Xueyan Han; Man Cao; Ruohan Wang; Jian Guo; Wei Sun; Jiarun Mi; Yuanli Liu; Tao Xue; Tianjia Guan (Journal of Hazardous Materials, 2025)

Graft copolymerization synthesis of chitosan-polyferric sulfate composite coagulant to improve biogas slurry treatment toward effective irrigation - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Guoxue Li; Wenhai Luo (Journal of Environmental Management, 2025)

Lab on a single microbead: An enzyme-free strategy for the sensitive detection of microRNA via efficient localized catalytic hairpin assembly - Yan Qi; Jiangtao Yu; Ming Lou; Yameng Yu; Ruohan Li; Zhenhao Zhang; Yuxuan Dai; Kejing Lao; Meng Cao; Xingchun Gou (Analytica Chimica Acta, 2025)

Generation of advanced glycation end products from glycated protein or fructose/glyoxal-protein adducts under in vitro simulated gastrointestinal digestion - Xiaojin Yuan; Shuqing Feng; Jianuo Li; Ruixin Guo; Chenxi Nie; Ruohan Zhai; Aobai Tu; Xinyu Cao; Min Zhang; Juxiu Li (Food Chemistry, 2025)

A novel chitosan and polyferric sulfate composite coagulant for biogas slurry pretreatment by simultaneous flocculation and floatation: Performance and underlying mechanisms - Ruohan Xia; Wancen Liu; Long D. Nghiem; Dingge Cao; Yun Li; Guoxue Li; Wenhai Luo (Water Research, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

Long-term exposure to the components of fine particulate matters and disability after stroke: Findings from the China National Stroke Screening Surveys - Hong Lu; Ruohan Wang; Jiajianghui Li; Mingkun Tong; Man Cao; Hengyi Liu; Qingyang Xiao; Yixuan Zheng; Yuanli Liu; Tianjia Guan; Tao Xue (Journal of Hazardous Materials, 2023)

Anisotropic In-Plane strain engineering Ni(OH)2 to activate alkaline hydrogen evolution reaction - Wenda Zhong; Ruohan Yu; Weilong Cao; Le Sun; Yi Yang; Ingo Manke; Chao Yang; Kangning Zhao (Chemical Engineering Journal, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Characteristics and Cause Analysis of Variations in Light Precipitation Events in the Central and Eastern Tibetan Plateau, China, During 1961–2019 - Kaifang Li; Liguo Cao; Zhengchao Zhou; Lei Jiao; Ning Wang; Ruohan Liu (Chinese Geographical Science, 2022)

Structural architecture of Neoproterozoic rifting depression groups in the Tarim Basin and their formation dynamics - Bizhu He; Cunli Jiao; Taizhu Huang; Xingui Zhou; Zhihui Cai; Zicheng Cao; Zhongzheng Jiang; Junwen Cui; Zhuoyin Yu; Weiwei Chen; Ruohan Liu; Xiaorui Yun; et al. (Science China Earth Sciences, 2019)

miRNAs play essential roles in the floral thermogenesis of Magnolia denudata (Magnoliaceae) - Xiangyu Liu; Dechang Cao; Xiangyu Ji; Zhixiang Zhang; Yanwei Wang; Ruohan Wang (Trees, 2015)